(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
The agrarian universe is usually explored by statements of scientific or technical genres, aimed at the specialized public. However, an episode of The Crown explores it in a peculiar way by presenting Queen Elizabeth II interested in horse breeding. The episode is the instance of analysis of this article, which aims to establish a reading about how the meanings of the agrarian domain circulate in urban environments, in fictional narrative audiovisual devices through the understanding of the circumstances in which technical terms, such as pasture management, are inserted in the enunciative plot. The enunciation scenes indicate conditions of production and attribution of meanings that are evaluated under the theoretical-methodological support of French discourse analysis. The study identifies the construction of contrasting narratives as a way of placing the topic of interest in the background, although it recognizes convergences in relation to the meanings constructed in the enunciation.